Health Status, Physical Disability, and Obesity Among Adult Mississippians With Chronic Joint Symptoms or Doctor-Diagnosed Arthritis: Findings From the Behavioral Risk Factor Surveillance System, 2003 - Carl W. Miller, PhD; Nadine T. James, RN, PhD; Peter J. Fos, PhD, DDS, MPH; Lei Zhang, MS, MBA, PhD; Peggy Wall, MS; Cindy Welch, RN, MSN (Centers for Disease Control and Prevention, 2008)
IntroductionThe purpose of this study was to analyze 2003 Mississippi Behavioral Risk Factor Surveillance System (BRFSS) data to describe the health of Mississippians with arthritis or chronic joint pain. For this study, we made statistical estimates of the extent of arthritis burden among the respondents and delineated measurable differences in sociodemographic factors, health status, and the prevalence of associated risk factors. Our findings compare health-related quality of life, physical activity, and key demographic characteristics and obesity rates, controlling for differences among the subgroups by age, sex, educational attainment, income, and race/ethnicity.MethodsRespondents to Mississippi's 2003 BRFSS were assigned to 1 of 5 distinct and mutually exclusive subgroups: 1) those with intermittent joint symptoms (IJS), 2) those with chronic joint symptoms (CJS), 3) those with doctor-diagnosed arthritis without CJS (DDA − CJS), 4) those with doctor-diagnosed arthritis with chronic joint symptoms (DDA + CJS), and 5) those with no joint symptoms (NJS). To determine the prevalence of arthritis and the continuum of disease progression, we compared the health-related quality of life, physical activity, and obesity of the respondents.ResultsRespondents with DDA + CJS were older than those with NJS (mean age, 57.1 years vs 38.7 years); they were more likely to be female (60.5% vs 51.7%), to have a high school diploma or less education (59.3% vs 45.4%), to be in fair to poor health (odds ratio [OR], 10.0), to be physically inactive (OR, 2.7), and to be overweight or obese (OR, 2.5).ConclusionHealth status, physical disability, and weight control may be substantially improved through heightened levels of physical activity. However, in spite of the potential for marked improvement, adult Mississippians, especially those clients with DDA + CJS, remain reluctant to commit to exercise regimens. Findings from this study suggest a need to encourage Mississippians with DDA + CJS to engage in some regular physical activity, which could reduce the damaging effects of disease and improve their health. Increasing the health care resources earmarked for arthritis self-help and physical activity programs is one potential avenue to address the problem.